Christ-faith and Abraham in Galatians 3-4: Paul's tale of two siblings - Harris, Johnathan F. (Biblical interpretation series, 2023)
Paul argues that Gentile Christians are true Abrahamic children apart from Torah because, like Isaac, they have been given life from the event of Christ-faith by the Spirit. Mere circumcision relates one to Abraham, like Ishmael, only by flesh.